Legal politics of the establishment of reserve funds for cemetery - Firman Firdausi; Willy Tri Hardianto; Asih Widi Lestari (Masyarakat, Kebudayaan dan Politik, 2022)
Malang City as one of the developed cities in Indonesia has a lot of development potential. Development in the city certainly has its own obstacles. Malang City is experiencing growth and an increase in population. This certainly affects all regional developments in this city. One of the obstacles to this development is a legal vacuum in the provision of a cemetery for the public interest which is carried out by local governments based on the Regional Government Law. This study aims to find out the gaps in the authority of local governments in land acquisition through the agenda of Reserve Funds and land acquisition in the public interest. This study used a normative legal method that takes regulatory data from the central to regional governments and analyzed it using legal theory and social analysis. This study concludes that the procurement of cemeteries by the local government can be carried out by means of a limited area of 5 hectares and can be submitted through a reserve fund. A reserve fund is established because large-scale developments cannot be completed in one fiscal year.